Temporal trend in the incidence of AIDS in people aged 50 and over in Brazil - Aenne Zandonadi Rodrigues Santana; Annelita Almeida Oliveira Reiners; Rosemeiry Capriata de Souza Azevedo; Janderson Diego Pimenta da Silva; Amanda Cristina de Souza Andrade; Priscila Aguiar Mendes (Universidade Federal de Santa Maria, 2021)
Objective: to analyze the temporal trend of the incidence of Acquired Immunodeficiency Syndrome (AIDS) in people aged 50 years or more in Brazil and its regions. Method: a mixed ecological study of reported cases of AIDS in people aged 50 years or more between 2007 and 2017, in Brazil and regions. Data were extracted from the National System of Diseases and Notification and analyzed using the Prais-Winsten method. Results: the temporal trend of the incidence of AIDS in people aged 50 years or more was stable in Brazil and the Southeast, South, and Midwest regions (annual percentage variation: 10.7; 4.9; 8.4 and 12.2, respectively); in the North and Northeast regions, it was increasing (annual percentage variation: 16.6 and 20.6, respectively). Conclusion: the incidence of AIDS in Brazil and the Southeast, South and Midwest regions were stable, as well as an increase in the incidence of the disease in the North and Northeast regions, in the population studied.